Exchange Rate Uncertainty in Money-Based Stabilization Programs - Morales, R. (IMF Working Papers; Working Paper, 1998)
Complementing the explanation provided by Calvo and Vegh (1994) for money-based stabilization programs, exchange rate uncertainty introduced to a particular version of the portfolio approach with imperfect competition in the banking system leads to a bias toward appreciation that is directly related to the divergence of expectations and that dampens the interaction between portfolio movements and the real exchange rate. Based on Frankel-Froot, uncertainty exists when the fundamental equilibrium real exchange rate is temporarily unknown in a foreign exchange market with two types of agents: 'parity-guessers,' who expect a jump to a reference parity level, and 'money-followers,' who expect nominal depreciation equal to the monetary rule.